Peran Solarisasi Tanah terhadap Pertumbuhan Patogen Tular Tanah dan Populasi Mikroba Tanah - Ramdan, Evan Purnama; Afriani, Astri; Hanif, Andini; Wati, Cheppy; Nurholis, Nurholis; Astuti, Dwi; Widodo, Widodo (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2022)
Soil-borne soil pathogens are pathogens that inhabit the soil and can survive for years in the soil, making them very difficult to control. Control with pesticides and fungicides harms the ecosystem, so other controls are needed such as soil solarization. This study aims to determine the growth response of soil-borne pathogens and soil microbial populations to soil solarization treatment. The study used a completely randomized design with 4 treatments consisting of solarization on soil media, solarization on soil and compost media, without solarization on soil media, and without solarization on soil media and compost on plastic trays. Each treatment was repeated 4 times. The soil-borne pathogens used were Sclerotium rolfsii and Rigidoporus lignisus. Each pathogen was planted in each planting medium with a depth of 5 and 10 cm. Then each tray is covered with 0.1 mm thick transparent plastic. Then given solarization treatment for four weeks. At the end of the observation, sclerotia and R. lignosus were grown on PDA media to be tested for pathogen survival and the solarization efficacy against pathogen growth was calculated. Soil samples from each treatment were also taken to calculate the soil microbial population. The results showed that soil solarization was able to suppress the growth of R. lignosus by 80-100% and S. rolfsii by 100%. Meanwhile, the microbes found in the soil solarization treatment consisted of groups of bacteria and fungi, respectively 7.67×104–1.90×107 CFU.mL-1 and 1.00×104–5.82×105 CFU.mL-1.